Spinal intramedullary tuberculoma following pulmonary tuberculosis: A case report and literature review. Issue 49 (December 2017) - Wang, Guan-Chyuan; Wu, Sheng-Wen
Abstract: Rationale: Spinal intramedullary tuberculoma (IMTB) is a rare disease that accounts for 1 to 2/100, 000 patients with tuberculosis. We presented a case with pulmonary tuberculosis and concurrent IMTB at C3 to C5 level and reviewed the recent case series and discussed the diagnosis, treatment, and outcome. Patient concerns: A 33-year-old male had concurrent pulmonary TB and IMTB at the C3 to C5 level. He had quadriplegia (muscle power 0 at 4 limbs) and sensory loss below C5 level. He also had incontinence, anal tone loss, and paradoxical respiratory pattern. Diagnosis: Spinal magnetic resonance imaging (MRI) showed a 25 11mm intramedullary lesion at C3/C4 level. Under the impression of IMTB, he underwent surgery. Intervention: We performed C3 to C5 laminectomy and en bloc removal of the tumor. The patient kept receiving anti-TB medications after the surgery. Outcome: His 4 limbs muscle power had improved but could not be liberated from the endotracheal tube, so tracheostomy was performed. Muscle power gradually increased to 3 points in his upper limbs and to 2 points in his lower limbs. Sensation in his 4 limbs gradually improved as well. Lessons: IMTB is a rare disease that should be treated with a combination of medication and surgery. For patients with prominent spinal cord compression and neurological symptoms, early operation to remove the tumor is necessary. Abstract : Supplemental Digital Content is available in the text